Psychosocial interventions for disruptive behavioural problems in children living in low- and middle-income countries: study protocol of a systematic review. Issue 5 (20th May 2015) - Burkey, Matthew D; Hosein, Megan; Purgato, Marianna; Adi, Ahmad; Morton, Isabella; Kohrt, Brandon A; Tol, Wietse A
Abstract : Introduction: Disruptive behaviour disorders (DBDs) are among the most common forms of child psychopathology and have serious long-term academic, social, and mental health consequences worldwide. Psychosocial treatments are the first line of evidence-based treatments for DBDs, yet their effectiveness often varies according to patient sociodemographic characteristics, practice setting, and implementation procedures. While a large majority of the world's children live in low- and middle-income countries (LMIC), most studies have evaluated psychosocial treatments for DBDs in high-income Anglo countries. Methods and analysis: The primary objective of this systematic review is to assess the effects of psychosocial treatments for DBDs in children and adolescents (under age 18) diagnosed with oppositional defiant disorder, conduct disorder, or other disruptive behavioural problems living in LMIC. The secondary objectives are to: (1) describe the range and types of psychosocial treatments used to address DBDs in LMIC and (2) identify key dissemination and implementation factors (adaptation processes, training/supervision processes, and financial costs). All controlled trials comparing psychosocial treatments versus waiting list, no treatment, or treatment as usual in children living in LMIC will be included. Studies will be identified using the methods outlined in the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines without restrictions on language, publication type, status, or date of publication. The primary outcome measures will be disruptive behavioural problems (eg, oppositionality, defiance, aggression or deceit). Secondary outcomes will be positive mental health outcomes (eg, prosocial behaviour), function impairment, institutionalisation (or hospitalisation), academic outcomes and caregiver outcomes. Ethics and dissemination: This study uses data from published studies; therefore ethical review is not required. Findings will be presented in a published manuscript. Trial registration number: PROSPERO CRD42014015334.